Effect of Blasting on the Strength of Rock Fragments - John Kemeny; Rennie Kaunda; David Streeter (International Society of Explosives Engineers, 2003)
This paper describes a field/laboratory study that was conducted in cooperation with a mine in Arizona. The primary purpose of the study was to investigate the effect of blasting energy on the crushability and grindability of the post-blast rock fragments. The crushability and grindability of the rock fragments were evaluated through laboratory comminution tests. A secondary purpose of the study was to investigate different laboratory methods for estimating the comminution properties of the rock fragments. In particular, a number of standard rock mechanics tests were conducted and compared with the comminution test results. Finally, the study was used to evaluate new technologies for estimating insitu rock mass strength and for assessing post-blast fragmentation. To estimate in-situ rock mass strength, the specific energy of drilling (SE) was calculated during blast hole drilling utilizing a continuous drill monitoring system. Post-blast fragmentation was estimated using the Split image processing system. Results from the study support the idea that increases in blast energy can enhance crushing and grinding. Also, several simple rock mechanics tests were found to correlate well with the results from standard comminution tests, which could prove to be useful in practice.